Sistem Kontrol Arduino Uno Pada Penggulingan Babi - Purwana Dana, Gusti Arya; Widhiada, I Wayan; Widiyarta, I Made (Teknik Desain Mekanika, 2022)
Abstractt Balinese people who have a pork guling culinary business still use traditional technology, namely using tamarind wood as a tool for rolling pigs and movinf it manually. Manually rolling this pig takes about 3 hours or more depending on the size of the pig. The time needed to make this pork guling is less efficient and costs a lot. The use of digital technology plays a very important role in the design of an automatic pig rolling device. This pig rolling machine will be driven by using an electric motor and using an Arduino-based control system. This arduino-based control system will control the rotational speed of the electric motor which is designed to rotate fast, medium and low. In the designed of this pork rolling machine, it will be able to increase the production of roasted pork rolls, a shorter time than before using traditional methods and lower costs. With the application of this pork roasting machine, it is hoped that it will help restaurant entrepreneurs to increase the production of pork guling and also increase the profits obtained based on the result of tests carried out on the Arduino Uno Control System on the Pig Rolling Machine useng the Open loop system control method, it can be concluded that the rise and fall of Rpm in caused by an imprecise load and loose chain on the pig rolling and using an open loop control system where, the control action does not depend on the control output, cannot compensate ot corret fot disturbances and the accuracy of the result depends on calibration. Keywords: Automatic Pig Overturning, Arduino Uno control system, Open Loop.